Defilement of Oil Quality of Final Drive Rear Right Excavator in Eleven-Ton Class Heavy Equipment Due to The Component Wear and Visualization on Website - Sukma, Rino; Nofriyandi; Guswandri; Kurnia, Rahmi Putri (SOTVI, 2023)
This research is part of the knowledge and skills of the S.O.S Scheduled Oil Sampling program conducted inPreventive Maintenance practical course in the distribution curriculum of D3 Heavy Equipment Engineering Study Program of Padang State Polytechnic[9]. Laboratory S.O.S Oil is a labor that could see the characteristics of the final drive oil completely, that the quality of the oil used to lubricate the system in final drive can be known as the condition of final drive. Data from S.O.S Oil Laboratory can be used as a reference in conducting in-depth analysis by engineer related to the condition of machine’s final drive. If the condition of the final drive can be known due the operation, it will ease the heavy equipment technicians to perform Preventive Maintenance. The writer’s current research will focus first on the analysis of oil quality defilement caused by wear of the components of final drive. The inner components of the final drive which streamed by lubricant are highly could cause wear and tear by friction between the materials operating in the final drive’s working system[5]. The oil on the final drive has specifications or properties that would affect final drive performance. The oli used in final drives uses single gread oils such as S.A.E 50, which are applied to final drives of eleven-ton excavators[6]. The wear of components in the final drive will be seen from the quality of the final drive oil, if the wear occurs is greater, the work of anti-wear additives on the oil is begins to decrease that there must be a solution and analysis obtained. Test results will be obtained based on test data from the S.O.S. Laboratory. The Laravel framework with Model-View-Controller (MVC) architecture is used to create this website for visualization the result.